Steel structures / Nurul Zafirah Jamaluddin - Jamaluddin, Nurul Zafirah (Universiti Teknologi MARA, Perak, 2019)
This practical training report describe about the experience gained during five months practical training period undertaken at Muara Atur (M) Sdn. Bhd. The purposed of this report is to studied and do research about steel structures. Being assigned under Civil and Structure, main task given is to get involved in any project and helped Project Engineer with some construction work. The main finding that had been studied was the installation method of steel structures for sports centre. This report will also look at the problems isolation taken for steel structures and it will focus on the solutions of the problems related in order to complete the tasks. This report also focus on about observation was performed at the site office especially with the Site Supervisor. This observation commonly being done at the site during working hours on weekdays. All the data is being recorded by written a short notes. The steel structures are important for this project because it has been used in most of the buildings for sports centre.